Physiological impacts of beech leaf disease across a gradient of symptom severity among understory American beech - McIntire, Cameron D. (Frontiers in Forests and Global Change, 2023)
Beech leaf disease (BLD) damage is associated with the parasitic nematode Litylenchus crenatae ssp. mccannii. Foliar symptoms manifest as darkened or chlorotic galls in the interveinal portions in the leaf, which become leathery and crinkled under high severity of infection. Though nearly a decade has passed since the discovery of this disease, little is known regarding the impact of BLD on leaf function and physiology. This study assesses the variation in leaf gas exchange and physiological leaf traits among asymptomatic and BLD-infected leaves across a gradient of symptom severity within a natural forested stand in central Connecticut, USA. Leaves with BLD symptoms are found to have significantly reduced carbon assimilation and instantaneous water use efficiency, with increased levels of stomatal conductance as symptom severity progresses. Leaf response to light manipulation is also affected, with an increase in dark respiration and the light compensation point among banded and crinkled leaves. Additionally, BLD symptoms are found to have a significant influence on leaf water content, specific leaf area, and leaf nitrogen content. Relationships between gas exchange and these leaf traits yield linear correlations that are used to infer functional relationships impacted by the disease.